Study of decision support for the installation of photovoltaic systems coupled to the electricity grid: Mali’s case study - Amadou Fousseyni Toure; Fadaba Danioko; Badié Diourte; Nouhoum Keita (Journal of Emerging Science and Engineering, 2025)
As the world's energy shortages worsen, countries are starting to exploit renewable energies for which solar power becomes the first choice. Considering the insufficiency of hydraulic and thermal resources in Mali, the hybrid system photovoltaic coupled at the grid is necessary and natural. The present study aims to increase the contribution of renewable energy sources to the national electricity production of Mali, and to pave the way for a good supply of electricity, ensuring the sustainable development of the economy and society of Mali. A preliminary analysis defines the technical, economic and environmental conditions for the implementation of 36 MW solar power plants at four points of Mali's energy interconnection network (Fana Kayes, Kita and Ségou). It can be a first contribution to demonstrating the feasibility of an integrated and self-sufficient energy model in this country. The power of 36 MW is compatible with the capacity of the interconnected network of Mali to absorb the electrical energy produced. For the location of the sites, several criteria have been taken into account for a definitive implementation (local climate conditions, proximity to the interconnected network, source of cooling water, social and environmental impact of the project). The results of the different simulations have shown that the installation of a solar system of 36 MW will be more beneficial in the cities of Ségou and Fana, less beneficial in the city of Kita compared to the two previous cities.